Identify numerical indicators to predict the performance of the crushing attacking skill in terms of some of the physical abilities of volleyball players. - Boussag, badreddine (sports creativity, 2025)
Crushing attack is one of the key offensive skills that contribute to winning games as this shot is designed to win a point, and the track of the ball during the beating is strong and fast, affecting the reaction of the rump wall. As the volleyball game develops, the orbic duties have increased, requiring the player to have high physical abilities. . For this purpose, this study gave training and volleyball specialists accurate digital indicators to predict the exact performance of this skill in terms of some of the studied physical abilities (explosive power of the two men, explosive power of the distinctive arm, speed, agility). This is in order to lay down the scientific foundations that contribute to the development of this skill